Digestive tract reconstruction after laparoscopic proximal gastrectomy: Double tract reconstruction or double flap technique? - Lindi Cai; Guanglin Qiu; Mengke Zhu; Shangning Han; Pengwei Zhao; Panxing Wang; Xiaowen Li; Xinhua Liao; Xiangming Che; Lin Fan (Annals of Gastroenterological Surgery)
Abstract Aim The reconstruction methods after proximal gastrectomy (PG) are varied but not standardized. This study was performed to evaluate the short‐term clinical outcomes between double tract reconstruction (DTR) and double flap technique (DFT). Methods We retrospectively reviewed and collected data of patients who underwent DTR and DFT after laparoscopic proximal gastrectomy (LPG), respectively, between January 2020 and March 2023. Propensity score matching (PSM) was used to balance the baseline data of the two groups, then we compared their short‐term clinical outcomes. Results A total of 72 patients (48 and 24 patients in the DTR and DFT groups, respectively) were included. The anastomosis time was significantly longer in the DFT group than that in the DTR group (70.1 vs. 52.7 min, p < 0.001). DFT was associated with shorter times of gas‐passing, start of diet, and postoperative length of hospital stay (p < 0.001). There were no significant differences between the two groups in terms of early and late postoperative complications (p = 0.710, p = 1.000, respectively). DFT was superior to DTR in maintaining body weight (p < 0.001), total protein (p = 0.011) and albumin levels (p = 0.018). As for QOL, DTR showed better results in the meal‐related distress subscale (p < 0.001). However, DFT was superior to DTR in terms of reducing diarrhea, constipation, and dumping related symptoms (p < 0.05). Conclusion Double flap technique emerged as a superior alternative to DTR in terms of facilitating early postoperative recovery, sustaining nutritional status, and improving QOL. DFT could potentially be the preferred reconstruction method following laparoscopic proximal gastrectomy.